K-Controllability and Approximate K-Controllability of Nonlinear Neutral Systems in Banach Spaces (Communications in Mathematical Research, 2021)
In this paper, K-controllability and approximate K-controllability of non-linear neutral differential equations in Banach spaces are studied. Sufficient conditionsare established for each of these types of controllability. The results are obtained byusing Leray-Schauder theory.
Keywords: K-controllability; approximate K-controllability; $m$-accretive operator; Mild solution; preassigned response.